Transformative urban governance: confronting urbanization challenges with geospatial technologies in Lagos, Nigeria - Dano, U.L. (Springer, 2020)
Lagos, the economic and industrial hub of Nigeria, is the second largest metropolitan area in Africa, and one of the fastest growing megacities in the world. It is indeed a paradoxical metropolis. On one hand, its strategic coastal location, economic potentials, and burgeoning population provideÂ livelihood opportunities to its teeming residents. On the other hand, its numerous urbanization challenges, including infrastructure decay, poor housing and slums, urban poverty, crimes, traffic congestion, and environmental problems can make living in the metropolis very difficult. This paper, therefore, reviews the major challenges facing the city and highlights the governmentâs recent interventions aimed at combating these problems. It suggests that effective utilization of geospatial technologies can help address the myriad of Lagosâ urban management challenges and promote urban sustainability. Â© 2019, Springer Nature B.V.